2011
DOI: 10.1111/j.1582-4934.2010.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and H1-histamine receptors faster venous circulation

Abstract: The study has analysed the action of histamine in the rabbit venous system and evaluated its potential role in contraction during increased venous pressure. We have found that a great variety exists in histamine sensitivity and H1-histamine receptor expression in various types of rabbit veins. Veins of the extremities (saphenous vein, femoral vein, axillary vein) and abdomen (common iliac vein, inferior vena cava) responded to histamine by a prominent, concentration-dependent force generation, whereas great th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In brief, vasoconstriction is the first response to a vascular injury, and is activated by second messengers like epinephrine that interact with adrenergic receptors and trigger the release of Ca 2+ of the sarcoplasmic reticulum that activates the calmodulin system in order to induce myogenic contractions. There are other second messengers that can activate the vasoconstriction in blood vessels like tromboxane A 2 (TA 2 ) that interacts with prostanoid receptors and shows effects also in hypertension [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, vasoconstriction is the first response to a vascular injury, and is activated by second messengers like epinephrine that interact with adrenergic receptors and trigger the release of Ca 2+ of the sarcoplasmic reticulum that activates the calmodulin system in order to induce myogenic contractions. There are other second messengers that can activate the vasoconstriction in blood vessels like tromboxane A 2 (TA 2 ) that interacts with prostanoid receptors and shows effects also in hypertension [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, from the point of view of scorpion venom pharmacology, the Scorpio maurus palmatus venom evolution regarding hemodynamics effects on blood pressure resembles evolutionary aspects of snake’s venoms. Since it has been reported that scorpion venoms induce mast cell degranulation and histamine release [14,15] and since histamine by activating H1 histamine receptor on endothelial cells [16] and generating nitric oxide produces vasodilation and fast hypotensive effects, we sought to investigate if the hypotensive effect of Scorpio maurus palmatus venom and isolated PlA 2 is mediated by histamine release in vitro (Figure 4) and in vivo (data not shown). Indeed, the Scorpio maurus palmatus venom similar to the reference compound 48/80 induced a dose-dependent degranulation and histamine release from mast cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, also low sensitivity may contribute to vasodilatation of post‐capillary resistance vessels. Galajda et al have shown that histamine contributes via H1 receptors to the tone of venous vessels . Experiments were done on isolated veins from rabbits, but the authors suggested similar reactions in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Subcutaneous histamine injections in rats evoked within five to ten minutes local constriction of veins, increased permeability, haemoconcentration and stasis in venules. Regarding vasodilatation in histamine wheals during the phase of re‐sensitization there can only be speculation based on the studies of Galajda et al mentioned above . Other factors of uncertainty are the varying effects of histamine on blood vessels of different vascular regions both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%